Effects on forest products markets of second-generation biofuel production based on biomass from boreal forests: a case study from Norway. Issue 3 (3rd April 2019) - Chudy, Rafał P.; Sjølie, Hanne K.; Latta, Greg S.; Solberg, Birger
ABSTRACT: Second-generation biofuels are often seen as essential element in the future bioeconomy strategy. Countries with extensive forest resources such as Norway often view wood as preferred bio-feedstock, yet the effects of wood demand on assortments of harvested wood and other wood-based industries are unclear. Focusing on the importance of feedstock choice, we analyse the impacts of establishing a second-generation medium-scale biofuel plant in Norway. For the analysis, a dynamic forest sector model where the choice of tree species, wood assortments, production of bioenergy, and forest industry products are explicitly included, was applied. We find the optimal biofuel feedstock mix to be dominated by softwood chips from pulpwood comprising 48% of total biomass inputs in 2030 and increasing to 67% by 2055, followed by hardwood chips from birch, comprising initially 34% of total biomass inputs and 16% by 2055. The proportion of harvest residues remained constant at about 18% over time and roundwood was not used at all for biofuel production. Despite the additional demand for chips, the single medium-scale biofuel plant will have only minor effects on existing forest industries and harvests in Norway, as the domestic impact is dampened by changes in foreign trade flows, especially of chips.